Consumption of oil macerated with garlic produces renovascular protective effects in adult apolipoprotein E-deficient mice. Issue 15 (7th July 2022) - Torres Palazzolo, Carolina; Martín Giménez, Virna Margarita; Mazzei, Luciana; De Paola, Matilde; Quesada, Isabel; Cuello Carrión, Fernando Darío; Fornés, Miguel Walter; Camargo, Alejandra Beatríz; Castro, Claudia; Manucha, Walter
Abstract : Organosulfur compounds could confer sunflower oil a beneficial effect and be considered as value-added nutraceuticals. Abstract : Oxidative stress and chronic inflammatory conditions contribute as key determinants in the development of vascular and renal diseases. Organosulfur compounds (OSCs) of oil macerated with garlic (OMG) are promising phytochemicals which could protect us from hyper-inflammation and oxidative stress-induced organ damage. The present work evaluated the effect of OMG intake in apolipoprotein E-knockout (ApoE-KO) mice. Adult female ApoE-KO mice were randomly divided into three groups and fed with control chow, oil-supplemented diet and OMG-supplemented diet. After 8 weeks, the animals were euthanized and blood, aorta, kidneys, liver and abdominal adipose tissues were obtained for further analysis. Biochemical parameters were measured in plasma, lipid peroxidation as malondialdehyde (MDA) levels was determined in the adipose tissue, oil red O was used to stain atherosclerotic lesions, and histological and ultrastructural analyses of the kidneys were performed. Renal expression levels of Tumor Necrosis Factor α (TNF-α), Interleukin-6 (IL-6) and Wilms' Tumor Protein (WT-1) were determined by western blotting and the co-immunoprecipitation assay (p53/WT-1). Also, transmission electron microscopy for studying the expression of mitofusin 2 (Mfn-2) was used to assess mitochondrial damage. The results showed that long-term moderate intake of OMG improved serum triglyceride levels, diminished the atheroma plaque area, and reduced lipid peroxidation. Furthermore, we found a decrease in oxidative and inflammatory markers, less apoptosis and reduced WT-1 expression in the kidneys. Also, OMG increased p53/WT-1 protein interactions and reduced mitochondrial damage. Our findings suggest that OMG intake would produce anti-atherosclerotic, antifibrotic, anti-inflammatory and antiapoptotic effects in adult ApoE-KO mice, conferring significant renovascular protective actions in a mechanism mediated, at least in part, by WT-1.